Use of e-module based on local potential projects to provide creative thinking abilities for high school students - Nisrina Nur Rahmi; Kusnadi Kusnadi; Yanti Hamdiyati (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Students have the ability to create solutions to problems based on local, national or global issues related to understanding biodiversity according to the demands at the end of learning. The solution to meet these demands is to conduct learning using e-modules based on local potential utilization projects. This study aims to obtain information on the use of e-modules based on local potential utilization projects to equip students with creative thinking skills. This learning is carried out using e-modules related to the syntax of project based learning (PjBL). Pre-experimental with one group pretest-posttest design. Participants in this study were 10th grade students consisting of 64 students. Data on students' creative thinking skills were obtained from the results of the pretest and posttest. The results of the study on students' creative thinking skills obtained an average N-Gain value of 0.56 which is included in the moderate category. Student responses related to the use of e-modules based on local potential utilization projects were obtained that 83.88% meant that almost all students said that e-modules could be used in learning. Based on the results of the study, the use of e-modules can be an alternative to improve students' creative thinking skills. Creative thinking skills possessed by students will increase students' creative abilities to innovate in order to utilize existing local potential.Abstrak. Siswa memiliki kemampuan menciptakan solusi atas permasalahan-permasalahan berdasarkan isu lokal, nasional atau global terkait pemahaman keanekaragaman hayati sesuai dengan  tuntutan diakhir pembelajaran. Solusi untuk memenuhi tuntutan tersebut dengan melaukan pembelajaran menggunakan e-modul berbasis proyek pemanfaatan potensi lokal. Penelitian ini bertujuan untuk memperoleh informasi mengenai penggunaan e-modul berbasis proyek pemanfaatan potensi lokal untuk membekalkan kemampuan berpikir kreatif siswa. Pembelajaran ini dilakukan dengan penggunaan e-modul yang terkait dengan sintaks project based learning (PjBL).  Pre- experimental dengan desain one group pretest-posttest. Partisipan dalam penelitian ini adalah siswa kelas 10 yang terdiri dari 64 siswa. Data kemampuan berpikir kreatif siswa diperoleh dari hasil pretest dan posttest. Hasil penelitian kemampuan berpikir kreatif siswa didapatkan nilai rata-rata N-Gain yaitu 0.56 yang termasuk kategori sedang. Respons siswa terkait dengan penggunaan e-modul berbasis proyek pemanfaatan potensi lokal didapatkan bahwa 83.88 % berarti hampir seluruh siswa mengatakan bahwa e-modul dapat digunakan dalam pembelajaran. Berdasarkan hasil penelitian penggunaan e-modul dapat menjadi alternatif untuk meningkatkan kemampuan berpikir kreatif siswa. Kemampuan berpikir kreatif yang dimiliki siswa akan meningkatkan kemampuan kreativitas siswa untuk melakukan inovasi untuk memanfaatkan potensi lokal yang ada.